Model components of forage-fed cattle systems: energy expenditure of grazing cattle and prediction of intake in dairy cows - Rochinotti, Diego (University of Florida, 2019)
Tesis para obtener el grado de Doctor of Philosophy, de la University of Florida (Estados Unidos), en 1998